Mr. and Mrs. God in the Creation Kitchen / Nancy Wood ; illustrated by Timothy Basil Ering. - Wood, Nancy C. (Candlewick Press, 2006)
In a very special kitchen, Mr. and Mrs. God cook up the planet Earth and some creatures to live there.